2021
DOI: 10.1002/bse.2769
|View full text |Cite
|
Sign up to set email alerts
|

Banks' business strategy and environmental effectiveness: The monitoring role of the board of directors and the managerial incentives

Abstract: The purpose of this paper is to investigate how banks' climate strategies affect environmental performance. To extend this line of research, the carbon disclosure of worldwide banks is examined. In particular, we focus on specific governance strategies: board of director monitoring and managerial incentives. Panel data are employed on a sample taken from 330 bank-year observations in the period after the financial crisis. The results show an increase in environmental performance through the implementation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 126 publications
(183 reference statements)
1
17
0
Order By: Relevance
“…Our research brings several contributions to the existing literature. First, our findings contribute to the current policy debate on the implications of climate change risk for the banking sector (Faiella & Malvolti, 2020; Galletta, Mazzù, & Naciti, 2021). Financial authorities recognise that climate change is not only a serious threat to economic well‐being but also an emerging financial risk that banks are called on to manage and minimise as soon as possible (Bolton et al, 2020; ESRB, 2020).…”
Section: Introductionsupporting
confidence: 52%
“…Our research brings several contributions to the existing literature. First, our findings contribute to the current policy debate on the implications of climate change risk for the banking sector (Faiella & Malvolti, 2020; Galletta, Mazzù, & Naciti, 2021). Financial authorities recognise that climate change is not only a serious threat to economic well‐being but also an emerging financial risk that banks are called on to manage and minimise as soon as possible (Bolton et al, 2020; ESRB, 2020).…”
Section: Introductionsupporting
confidence: 52%
“…The choice of the dependent variables came from the willingness to investigate the financial, social, and environmental dimensions of corporate performance in banks. Improving financial performance is not the only objective of banks; indeed, to attract more investors, financial institutions must enhance the other performance dimensions that can affect investors' decisions and stakeholders' needs, developing a competitive advantage to be socially beneficial (Galletta, Mazzù, & Naciti, 2021; García‐Sánchez et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Along with other polluting industries, financial institutions are involved in environmental responsibility (Gallego‐Álvarez & Pucheta‐Martínez, 2019; Galletta, Mazzù, & Naciti, 2021). Therefore, with the purpose of testing our third set of hypotheses, we employ policy emission reduction as a proxy for the dependent variable, which indicates environmental performance (ENV_PERF).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, it has been suggested that one way by which the SDGs can be attained is to encourage senior managers of firms to implement sustainable banking initiatives (Galletta et al, 2021; Haque, 2017). More importantly, a valuable link of enhancing the accountability of senior managers to sustainable banking is to tie improvements to their compensation (Cordeiro & Sarkis, 2008; Haque & Ntim, 2018; Haque & Ntim, 2020).…”
Section: Introductionmentioning
confidence: 99%